INNOVATIVE METHODOLOGICAL APPROACHES TO FOREIGN LANGUAGE TEACHING WITHIN THE DUAL EDUCATION SYSTEM IN VOCATIONAL EDUCATION - Jabborberganova Hurriyat, (TADQIQOTLAR, 2026)
Abstract:  This  essay  investigates  innovative  methodological  approaches  for teaching  foreign  languages  within  the  context  of  the  dual  education  system  in vocational  education.  It  explores  how  dynamically  merging  theory  and  practice—central  to  dual  education—necessitates  new  language  pedagogy  paradigms  that connect classroom learning with real-world professional requirements. The discussion highlights  integrative  curricular  strategies,  technology-enhanced  methodologies, student-centered  learning  environments,  and  multifaceted  assessment  practices  as means to optimize language acquisition in vocational contexts. Drawing from recent research  and  practical  experiences,  particular  emphasis  is  given  to  communicative competence,  intercultural  awareness,  career-specific  language  needs,  and  the synergistic  role  of  partnerships  between  educational  institutions  and  industry.  The conclusion  summarizes  the  key  findings  and  implications  for  educators  and policymakers, while the reference list offers a foundation for further inquiry.